First- and second-generation migrants in Germany: what do we know and what do people think - Fertig, Michael; Schmidt, Christoph M. (Discussion paper series, 2001)
This paper provides a snapshot of the stock of immigrants in Germany using the 1995 wave of the Microzensus with a particular emphasis on distinguishing first- and second-generation migrants. On the basis of this portrait, we draw attention to the empirically most relevant groups of immigrants and review the received literature on economic migration research in the three principal avenues of migration research. The aspect which we concentrate on in our empirical application, the welfare dependence of immigrants, is a matter of intense debate among economists and policy makers. We contrast the very moderate actual public transfer payment dependence of migrants to Germany with the perception of migrants dependence on public assistance by Germans from various population strata.
Literaturverz. S. 27 - 30
Keywords: 1995; Arbeitspapier; Graue Literatur